Using Mac OS X Lion - Johnson, Yvonne (Pearson Education, Inc., 2012)
A guide to the features of Mac OS X Lion covers such topics as creating a user account, using the system profiler, managing applications, browsing the Web, using TextEdit, using widgets, importing music, using iChat and FaceTime, and encrypting data.